2015
DOI: 10.1007/s00289-015-1479-0
|View full text |Cite
|
Sign up to set email alerts
|

Quaternized poly(1-vinylimidazole) hydrogel for anion adsorption

Abstract: Poly(1-vinylimidazole) (PVIm) hydrogels were synthesized through free radical polymerization/crosslinking of 1-vinylimidazole (VIm) in aqueous solutions with azobisisobutyronitrile (AIBN) used as the initiator and N,N 0 -methylenebisacrylamide (MBAAm) as the crosslinking agent. To quaternize PVIm, dimethylsulfate was used as the methylating agent. Pristine and quaternized PVIm hydrogels were characterized by spectroscopic techniques. Finally, ground hydrogels were used in anion adsorption. The amount of anion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…It can be seen that the intensities of the absorption bands around 2958 and 2853 cm À1 (C-H stretching) significantly increased and the characteristic absorption bands of imidazolium rings around 1571 and 1552 cm À1 appeared after the quaternization reaction indicating that the quaternization indeed occurred. 37,42,43 The 1 H NMR spectra of the PVI and the QPVI are shown in Figure 3. For the PVI, the broad peak at 1.98 ppm is assigned to the protons of the methylene groups (CH 2 ) of the main chain.…”
Section: Polymer Synthesismentioning
confidence: 99%
“…It can be seen that the intensities of the absorption bands around 2958 and 2853 cm À1 (C-H stretching) significantly increased and the characteristic absorption bands of imidazolium rings around 1571 and 1552 cm À1 appeared after the quaternization reaction indicating that the quaternization indeed occurred. 37,42,43 The 1 H NMR spectra of the PVI and the QPVI are shown in Figure 3. For the PVI, the broad peak at 1.98 ppm is assigned to the protons of the methylene groups (CH 2 ) of the main chain.…”
Section: Polymer Synthesismentioning
confidence: 99%
“…It was found that p-VIm showed a remarkable affinity to Hg(II) cations and also completely removal of mercury cations was achieved at pH 2.0. In another work by Genç et al (2016), a quaternized p-VIm hydrogel was employed in adsorption of fluoride, bromide, nitrite, nitrate, phosphate and sulfate anions. They demonstrated that the anion adsorption by p-VIm was negligible compared to that quaternized p-VIm.…”
Section: Introductionmentioning
confidence: 99%
“…Son yıllarda, vinil imidazol (VI) bazlı hidrojeller, imidazol halkası üzerindeki elektron sağlayıcı azot atomu tarafından farklı moleküler parçalara güçlü bir bağlanma eğilimi göstermesi ve zayıf baz karakterine sahip imidazol grupları kolayca protonlanarak pH'a bağlı hacim değişim davranışı sergilemesi nedeniyle büyük ilgi haline gelmiştir [19], [20]. VI içeren hidrojellerde, bulundukları ortamın asitlik derecesinin artmasıyla polimer zincirleri arasında meydana gelen elektrostatik itmenin artışına bağlı olarak su moleküllerinin ağ yapı içerisine difüzyonu kolaylaşır ve hidrojelin şişme kapasitesinde artış meydana gelir.…”
Section: Introductionunclassified